2018
DOI: 10.1016/j.pharmthera.2018.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity mechanisms of the combination of BRAF-inhibitors and MEK-inhibitors

Abstract: a b s t r a c t a r t i c l e i n f oMany new drugs have appeared in last years in the oncological treatment scenario. Each drug carries an important set of adverse events, not less, cardiovascular adverse events. This aspect is even more important considering the increasing use of combination therapies with two drugs, or three drugs as in some ongoing clinical trials. Besides it represents a growing problem for Cardiologists, that face it in every day clinical practice and that will face it probably more and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…In the phase III COMBI-d trial, treatment related cardiac adverse events were reported as decrease in left ventriclar ejection fraction in 5% of patients. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the phase III COMBI-d trial, treatment related cardiac adverse events were reported as decrease in left ventriclar ejection fraction in 5% of patients. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
“…The BRAF inhibitors are reported to cause hypertension, and QT interval prolongation as seen on ECG. [ 3 ] Unlike Dabrafenib we have reports of vemurafenib induced pericarditis associated with effusions and cardiac tamponade. [ 7 ] Mahoney et al demonstrated that appropriate treatment of cardiac tamponade and vemurafenib discontinuation, resulted in complete resolution with the ability to resume treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations